Β2‐AR activation promotes cleavage and nuclear translocation of Her2 and metastatic potential of cancer cells. Issue 12 (27th October 2020) - Liu, Dan; Zha, Li; Liu, Yuchen; Zhao, Xuan; Xu, Xiyue; Liu, Shuci; Ma, Wen; Zheng, Junnian; Shi, Ming
Abstract: Prolonged hypersecretion of catecholamine induced by chronic stress may correlate with malignant progression of cancer. β2‐adrenergic receptor (β2‐AR) overexpressed in certain cancer cells may translate the signals from neuroendocrine system to malignant signals by interacting with oncoproteins, such as Her2. In the present study, we demonstrate that catecholamine stimulation activates the expression and proteolytic activity of ADAM10 by modulating the expression of miR‐199a‐5p and SIRT1 and also confirm that catecholamine induction triggers the activities of γ‐secretase, leading to shedding of Her2 extracellular domain (ECD) by ADAM10 and subsequent intramembranous cleavage of Her2 intracellular domain (ICD) by presenilin‐dependent γ‐secretase, nuclear translocation of Her2 ICD, and enhanced transcription of tumor metastasis‐associated gene COX‐2 . Chronic stimulation of catecholamine strongly promotes the invasive activities of cancer cells in vitro and spontaneous tumor lung metastasis in mice. Furthermore, nuclear localization of Her2 was significantly correlated with overexpression of β2‐AR in human breast cancer tissues, indicating that catecholamine‐induced β2‐AR activation plays decisive roles in tumor metastasis. Our data also reveal that an unknown mechanism by which the regulated intramembrane proteolysis (RIP) initiated by β2‐AR‐mediated signaling controls a novel Her2‐mediated signaling transduction. Abstract : In the present study, we demonstrated that catecholamine stimulation activates the expression and proteolytic activity of ADAM10 by modulating the expression of miR‐199a‐5p and SIRT1 and also confirm that catecholamine induction triggers the activities of γ‐secretase, leading to shedding of Her2 ECD by ADAM10 and subsequent intramembranous cleavage of Her2 ICD by presenilin‐dependent γ‐secretase, nuclear translocation of Her2 ICD, and enhanced transcription of tumor metastasis‐associated gene COX‐2. Chronic stimulation of catecholamine strongly promotes the invasive activities of cancer cells in vitro and spontaneous tumor lung metastasis in mice. Furthermore, the nuclear localization of Her2 was significantly correlated with overexpression of β2‐adrenergic receptor (β2‐AR) in human breast cancer tissues, indicating that catecholamine‐induced β2‐AR activation plays decisive roles in tumor metastasis.